2021
DOI: 10.18844/cjes.v16i2.5638
|View full text |Cite
|
Sign up to set email alerts
|

Women and leadership style in school management: Study of gender perspective

Abstract: Women’s representation in leadership positions is still low because there is still an opinion that women are not worthy of being leaders and only men are worthy of being leaders. This condition proves women’s low participation in leadership roles because the patriarchal culture still strongly influences people’s perspective. This paper aims to describe the roles and positions of women in school management. The research data are in the form of observations and interviews with female school principals and four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
4
0
7
Order By: Relevance
“…It also helps in employee engagement and retention (Rosener, 1995). It is also found that women are more collaborative and manage business in more democratic ways (Dai et al, 2011; Mulawarman et al, 2021). The efficacy of a woman leader as the chairperson has a positive impact on a board’s decision-making process.…”
Section: Resultsmentioning
confidence: 99%
“…It also helps in employee engagement and retention (Rosener, 1995). It is also found that women are more collaborative and manage business in more democratic ways (Dai et al, 2011; Mulawarman et al, 2021). The efficacy of a woman leader as the chairperson has a positive impact on a board’s decision-making process.…”
Section: Resultsmentioning
confidence: 99%
“…Pekerjaan yang hanya mengurus kegiatan rumah tangga menyebabkan perempuan dianggap sebagai penerima pasif pembangunan, dikatakan sebagai penerima pasif karena keterbatasan yang dimiliki oleh ibu rumah tangga seperti peluang dan kesempatan yang masih terbatas dalam mengelola sumber daya, keterampilan dan pendidikan yang rendah. Ada anggapan terkait dengan perempuan yaitu perempuan tidak sama dengan lakilaki karena laki-laki adalah kepala keluarga (Mulawarman et al, 2021). Perempuan masih mengalami diskriminasi dari segala aspek kehidupan (Abdurrahman & Tusianti, 2021).…”
Section: Pendahuluanunclassified
“…With the togetherness in preparing the programme, all parties will feel appreciated and will be able to eliminate misunderstandings between the principal and the teacher. Following the school's management, the principal involves the school community in the planning of the programme so that all are responsible for the implementation of the school programme (Mulawarman et al, 2021).…”
Section: Planningmentioning
confidence: 99%